The Theme Analysis in Pride and Prejudice: By Jane Austen - Anastasia Usman, Happy; Mahmud, Musfira; Simbuka, Srifani (Language Development Center, 2022)
Background: This study analyzes the themes in 'Pride and Prejudice' by Jane Austen. Purpose: The purpose of this study is to determine the theme of 'Pride and Prejudice. Method: This study uses descriptive method and intrinsic approach. This research analyzes the theme, character, characterization, plot, setting, and point of view in the novel. To support this approach, the researcher applied objective theory which is based on library research, things that happen in a work are oriented to the work itself. The research data is taken from 'Pride and Prejudice. Based on the data analysis, the theme of love and arrogance of Pride and Prejudice. Results and Discussion: The result of this study is that humans generally face and feel many things in life. Everyone has feelings of love. Some people can easily express their feelings to others, but some others cannot express them because they are shy, or even become arrogant. It also happens in the love story of the characters in 'Pride and Prejudice by Jane Austen. Conclusions and Implications: This research gives the message that; If we love someone, it should be expressed, and should not be hidden or harbored. Let us not hate someone because we will never know the feeling of hate that will make us love. Let us not be arrogant or haughty towards others as these traits will alienate us from others. Be kind to others so that by being kind to others we will be far from being called arrogant or haughty. The implication of this research is the importance of expressing feelings of love and not keeping them hidden or suppressed, as this can prevent unnecessary hatred and conflict. Hatred towards someone can turn into love, so avoiding hate is essential in maintaining harmonious relationships.